2021
DOI: 10.1111/ced.14788
|View full text |Cite
|
Sign up to set email alerts
|

What’s new in atopic eczema? An analysis of systematic reviews published in 2019. Part 1: Risk factors and prevention

Abstract: Summary This review is part of an annual evidence update on atopic eczema (AE), providing a summary of key findings from 18 systematic reviews published in 2019 on AE risk factors and prevention. Parental atopy, particularly AE, is a risk factor for offspring AE, and this risk is augmented both by the number of parental atopic diseases present and the number of affected parents. Low‐quality evidence suggests that autumn or winter birth increases childhood AE risk compared with birth in spring. There is some ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
3
0
0
Order By: Relevance
“…In line with our results, they found the risk of AD was greater in children exposed to prenatal antibiotics than in those who were not exposed (aHR 1.10, 95% CI 1.09–1.12), whereas no such increased risk was found in the sibling‐control analysis, suggesting some familial confounders 25 . Based on the covariates they adjusted for, we further adjusted the maternal comorbidities, maternal AD, maternal allergic rhinitis, gestational infections, and maternal acetaminophen use during pregnancy, which may be potential risk factors according to previous studies 12,26,27 . In addition, their study revealed an apparent dose–response relationship and the category of infection did not modify the association of maternal antibiotic use and child AD, which was consistent with our results.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In line with our results, they found the risk of AD was greater in children exposed to prenatal antibiotics than in those who were not exposed (aHR 1.10, 95% CI 1.09–1.12), whereas no such increased risk was found in the sibling‐control analysis, suggesting some familial confounders 25 . Based on the covariates they adjusted for, we further adjusted the maternal comorbidities, maternal AD, maternal allergic rhinitis, gestational infections, and maternal acetaminophen use during pregnancy, which may be potential risk factors according to previous studies 12,26,27 . In addition, their study revealed an apparent dose–response relationship and the category of infection did not modify the association of maternal antibiotic use and child AD, which was consistent with our results.…”
Section: Discussionsupporting
confidence: 84%
“…25 Based on the covariates they adjusted for, we further adjusted the maternal comorbidities, maternal AD, maternal allergic rhinitis, gestational infections, and maternal acetaminophen use during pregnancy, which may be potential risk factors according to previous studies. 12,26,27 In addition, their study revealed an apparent doseresponse relationship and the category of infection did not modify the association of maternal antibiotic use and child AD, which was consistent with our results. In terms of the trimester-specific association between antibiotic exposure during pregnancy and childhood AD, their results were comparable with our results in that the risk increased in all trimesters; however, our data showed a slightly higher risk in the first and second trimesters compared with the third trimester, which might be explained by antibioticsrelated dysbiosis or immunomodulatory effects, phenomena that are known to have a greater impact during early pregnancy.…”
Section: F I G U R E 1 Kaplan-meier Curvessupporting
confidence: 91%
“…24 Based on the covariates they adjusted for, we further adjusted the maternal comorbidities, maternal AD, maternal allergic rhinitis, gestational infections, and maternal acetaminophen use during pregnancy, which may be potential risk factors according to previous studies. 12,25,26 In addition, their study revealed an apparent doseresponse relationship, and the category of infection did not modify the association of maternal antibiotic use and child AD, which was consistent with our results. In terms of the trimester-specific association between antibiotic exposure during pregnancy and childhood AD, their results were comparable with our results in that the risk increased in all trimesters; however, our data showed a slightly higher risk in the first and second trimesters compared with the third trimester, which might be explained by antibiotics-related dysbiosis or immunomodulatory effects, phenomena that are known to have a greater impact during early pregnancy.…”
Section: Comparison With Other Studiessupporting
confidence: 91%